2015
DOI: 10.1002/oby.21044
|View full text |Cite
|
Sign up to set email alerts
|

Nulliparity is associated with less healthy markers of subclinical cardiovascular disease in young women with overweight and obesity

Abstract: Objective Higher parity is associated with increased subclinical cardiovascular disease (CVD) in mid-life and older women, and with increased CVD risk overall. The relationship between parity, subclinical CVD, and infertility in overweight and obese young women has been infrequently evaluated. Methods Reproductive histories were obtained in 191 (73%) overweight and obese (BMI 25 – 39.9 kg/m2) young women participating in a weight loss trial. Baseline carotid intima-media thickness (IMT) and inter-adventitial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, continued ER stress activates the downstream factors of the PERK pathway, such as pro-apoptotic gene C/EBP homologous protein (CHOP), and causes apoptosis and cell death ( 46 , 51 , 52 ). UPR can also potentiate the EMT of gastric cancer cells under situations of severe hypoxia ( 53 ). In current study, it was found that matrine time-dependently increased Bip, p-eIF2α, ATF4 and CHOP expression in DU145 and PC-3 prostate cancer cells, and increased Bip and ATF4 expression in prostate cancer tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, continued ER stress activates the downstream factors of the PERK pathway, such as pro-apoptotic gene C/EBP homologous protein (CHOP), and causes apoptosis and cell death ( 46 , 51 , 52 ). UPR can also potentiate the EMT of gastric cancer cells under situations of severe hypoxia ( 53 ). In current study, it was found that matrine time-dependently increased Bip, p-eIF2α, ATF4 and CHOP expression in DU145 and PC-3 prostate cancer cells, and increased Bip and ATF4 expression in prostate cancer tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that reproductive factors may affect women's health in later life. 14 A recent meta-analysis 5 revealed that an increasing number of parity was associated with a linearly reduced hip fracture risk, while another meta-analysis 6 indicated that higher parity was significantly associated with an increased risk of type 2 diabetes. Cardiovascular disease (CVD) is the leading cause of death in American women 7 and in Chinese middle-aged and older women.…”
Section: Introductionmentioning
confidence: 99%
“…Women who have had 2 or 3 births have the lowest cardiovascular mortality rate compared with women with less than 2 or more than 4 births [ 2 ]. Furthermore, women who have had 2–3 births have less evidence of subclinical atherosclerosis (reduced carotid intima-media thickness; cIMT, coronary artery calcium; CAC, and increased carotid distensibility) compared with women who have had less than 2 or 4 or more births years later [ 3 5 ]. Taken together, these data suggest that experiencing 2–3 pregnancies may reduce cardiovascular risk during aging in women.…”
Section: Introductionmentioning
confidence: 99%